2015
DOI: 10.1039/c5rp00136f
|View full text |Cite
|
Sign up to set email alerts
|

Flipped learning in higher education chemistry: emerging trends and potential directions

Abstract: Flipped learning has grown in popularity in recent years as a mechanism of incorporating an active learning environment in classrooms and lecture halls. There has been an increasing number of reports for flipped learning in chemistry at higher education institutions. The purpose of this review is to survey these reports with a view to examining the rationale for adopting the flipped learning approach, how educators have implemented the flipped learning approach into their own practice and how these implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
271
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(300 citation statements)
references
References 50 publications
15
271
0
14
Order By: Relevance
“…We found that 95% of the students were satisfied to some degree with this format of learning. This suggests that flipped learning can be an effective educational approach for delivery of analytical chemistry as shown for other areas of chemistry [5,8]. Table 1 shows show the students' perceived strengths of flipped learning.…”
Section: Usefulness Of and Satisfaction With The Flipped Learning Modelmentioning
confidence: 85%
See 2 more Smart Citations
“…We found that 95% of the students were satisfied to some degree with this format of learning. This suggests that flipped learning can be an effective educational approach for delivery of analytical chemistry as shown for other areas of chemistry [5,8]. Table 1 shows show the students' perceived strengths of flipped learning.…”
Section: Usefulness Of and Satisfaction With The Flipped Learning Modelmentioning
confidence: 85%
“…Most studies generally highlight the benefits of flipped learning, with the most significant being the ability to develop active learners [3][4][5]; however, others are sceptical, querying its efficacy in the lack of perceived gains in terms of grades [6] and resources needed to develop and deliver flipped learning [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alanyazın incelendiğinde bu bulguyu destekleyen çalışmalara rastlanmıştır. Örneğin, Seery, (2015) kimya öğretiminde ters yüz edilmiş öğrenmeyi kullanan araştırma raporlarını incelemiştir. Araştırma sonuçları genel anlamda TES modelinin öğrencilerin kimya ders başarısı üzerinde olumlu etkiye sahip olduğunu ortaya koymaktadır.…”
Section: Tartişma Ve Sonuçunclassified
“…Alanyazın incelendiğinde, TES modelinin matematikten (DeSantis, Van Curen, Putsch ve Metzger, 2015), kimya öğretimine (Schultz, Duffield, Rasmussen ve Wageman, 2014;Trogden, 2015) dil öğretiminden (Başal, 2015, Helgeson, 2015 fizik öğretimine (Kettle, 2013) kadar birçok ders de çalışıldığı anlaşılmaktadır. İlgili çalışmalar, TES modelinin pratiğinden (Hibbard, Sung ve Wells, 2016;MacKinnon, 2015;Maxson ve Szanislo, 2015;Pearson, 2013;Prashar, 2015;Sharma, Lau, Doherty ve Harbutt, 2015;Smith, 2013), teorisine (Filiz ve Kurt, 2015;Karadeniz;Mehring, 2016;Nederveld & Berge, 2015;Seery, 2016;Temizyürek ve Ünlü, 2015) geniş bir alana yayıldığı söylenebilir.…”
Section: İlgili Alanyazın Taramasıunclassified